Identification of maximum volume in strength training. Part 1: Maximum number of repetitions - Desgorces, F.-D.; Laffite, L.; Testa, M. (First international symposium sciences and practices in swimming, 2006)
Our study aimed to determine and discuss the capacity to repeat lifts in swimmers compared to rowers and power-lifters. We assessed the one repetition maximum (1-RM) and maximum number of repetitions (MNR) at 85, 75, 60, 40 % of 1-RM in bench press. Compared to power-lifter and rowers, swimmers presented low 1-RM and high muscular endurance at light relative loads (60 and 40 % of 1-RM). Relationships appeared between MNR and races duration and between the total load lifter (load x MNR) at 40 % of 1-RM suggesting specific adaptations to swim requirements and/or individual characteristics influences. Increase of 1-RM in respect to the endurance profile required could lead to an enhanced total load lifted and then to sport performance.